International investment and national security review - Ma, J (Vanderbilt University Law School, 2019)
National security is a pillar of international law. As long as sovereign states exert power within the international legal regime, national security will be an exception to international law. These security concerns also come to light in the international investment legal regime. The international investment legal regime provides for essential security exceptions, aiming at protecting host states' interests. This practice has been honored by international investment treaties and international investment tribunals. Although such exemption provisions can balance the interests between international investors and host states, they might be abused by host states in virtue of rising protectionism. Today, with respect to international investment, worldwide protectionism is rising under the guise of national security. Can domestic courts or international tribunals examine the process of national security review conducted under a relevant national committee? If yes, how should domestic courts or international tribunals evaluate the process of national security review? If no, what are the alternatives to prevent the abuse of application of national security grounds? In the international investment legal regime, the issue of how to balance essential security interests and foreign investors' interests has not been resolved until now. Aiming to fill this gap, this Article answers those questions with a comprehensive study of how to deal with national security issues in different phases of international investment. This Article makes three contributions. First, it distinguishes national security issues in the pre -establishment phase and the post-establishment phase. Moreover, it distinguishes non-self-judging essential security clauses and selfjudging essential security clauses in international investment agreements. Building upon these differences, this Article provides different methodologies to deal with national security review. Second, rejecting the popular "good faith" methodology to review national security decisions by international tribunals, this Article provides an alternative to deal with national security issues involving foreign investment-a model of compensation. Third, this Article offers some thoughts on how adjudicators and policy makers should think about national security in international investment law.